2015
DOI: 10.1007/s00204-015-1625-3
|View full text |Cite
|
Sign up to set email alerts
|

Methyleugenol and oxidative metabolites induce DNA damage and interact with human topoisomerases

Abstract: Methyleugenol is a substituted alkenylbenzene found in several herbs and spices. It is classified by the European Union's Scientific Committee on Food as a genotoxic carcinogen. We addressed the biological mechanism of the genotoxic properties of methyleugenol and its oxidative metabolites. Methyleugenol and the oxidative metabolites significantly enhanced the DNA damage in human colon carcinoma cells (HT29). Methyleugenol did not affect the protein status of γH2AX, a biomarker of DNA double-strand breaks, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…). Methyleugenol, present in various herbs and spices and widely used in food industry, has been shown to be genotoxic in colonocytes (Groh et al., ). Linalool is a major compound in basil and coriander and has been found to be genoprotective against oxidative DNA damage in hepatocytes (Mitić‐Culafić et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Methyleugenol, present in various herbs and spices and widely used in food industry, has been shown to be genotoxic in colonocytes (Groh et al., ). Linalool is a major compound in basil and coriander and has been found to be genoprotective against oxidative DNA damage in hepatocytes (Mitić‐Culafić et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Thymol and eugenol are important EOC and their genotoxicity and genoprotection against oxidative DNA damage has been demonstrated (Horváthová et al 2014). Methyleugenol, present in various herbs and spices and widely used in food industry, has been shown to be genotoxic in colonocytes (Groh et al, 2016). Linalool is a major compound in basil and coriander and has been found to be genoprotective against oxidative DNA damage in hepatocytes (Mitić-Culafić et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of DNA adduction and DNA damage induced by ME has been the focus of intensive investigations . However, relatively less effort has been directed toward the understanding of the molecular details involved in ME-derived protein covalent binding and possible toxicological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Methyleugenol and its metabolites, 1′-hydroxymethyleugenol, methyleugenol-2′,3′epoxide and 3′-oxomethylisoeugenol exhibited DNA strand breaks in human colon adenocarcinoma cells HT29, whereas the metabolites showed stronger DNA damaging properties than methyleugenol itself, probably due to the high enzymatic activity of HT29 cells. Moreover, 3′-oxomethylisoeugenol was identified as topoisomerase Iand human histone deacetylase-inhibitor, which additionally contribute to DNA damage [92]. In several in vitro and in vivo studies on rodents, methyleugenol showed genotoxic and carcinogenic effects.…”
Section: Methyleugenolmentioning
confidence: 99%